The Pan American Health Organization and international health: a history of training, conceptualization, and collective development. - Auer, Annella; Espinel, Juan Eduardo Guerrero (Pan American Journal of Public Health / Revista Panamericana de Salud Pública, 2011)
A constantly changing and increasingly complex global environment requires leaders with special competencies to respond effectively to this scenario. Within this context, the Pan American Health Organization (PAHO) goes beyond traditional leadership training models both in terms of its design as well as its conceptual approach to international health. As an intergovernmental, centenary organization in health, PAHO allows participants a unique vantage point from which to conceptualize, share experiences and develop projects relevant to international health. Derived from over two decades of experience (1985-2006) training professionals through its predecessor Training Program in International Health, the Leaders in International Health Program "Edmundo Granda Ugalde" (LIHP) utilizes an innovative design, virtual and practical learning activities, and a problem-based approach to analyze the main concepts, theories, actors, forces, and processes relevant to international health. In collaboration with PAHO/ WHO Representative Offices and national institutions, participants develop country projects based on priority health issues, many of which are integrated into the Organization's technical cooperation and/or implemented by relevant ministries and other entities in their respective countries/subregions. A total of 185 participants representing 31 countries have participated in the LIHP since its inception in 2008, building upon the 187 trained through its predecessor. These initiatives have contributed to the development of health professionals in the Region of the Americas devoted to international health, as well as provided important input towards a conceptual understanding of international health by fostering debate on this issue.